Pengaruh Paritas Daya Beli, Paritas Suku Bunga Terhadap Nilai Tukar Rupiah Dan Dollar Amerika Serikat Periode 2020-2024 - Dini Nurhandayani; Pujiyanti Pujiyanti; Yusup Murdani; Perwito Perwito (Indonesia Economic Journal, 2026)
Exchange rates react to changes in inflation and interest rates. There are at least three theories explaining the relationship between inflation, interest rates, and exchange rates: purchasing power parity, interest rate parity, and the international Fisher effect. This study aims to examine the influence of purchasing power parity, interest rate parity, and the international Fisher effect on the rupiah exchange rate against the US dollar. The study population includes time series data on inflation, nominal interest rates, real interest rates, and the rupiah exchange rate. Secondary data used are quarterly reports on inflation, nominal interest rates, real interest rates, and the rupiah exchange rate. The independent variables used are purchasing power parity, interest rate parity, and the international Fisher effect. Meanwhile, the dependent variable used is the rupiah exchange rate against the US dollar. The results of this study indicate that purchasing power parity and interest rate parity simultaneously have a significant influence on the rupiah/US dollar exchange rate.